Bringing Culinary Justice to the Table: A Conceptual Approach to Enrich the Debate on Food Justice - Brückner, Meike; Hoinle, Birgit (DIE ERDE – Journal of the Geographical Society of Berlin, 2025)
The concept of food justice is widely used in urban geography and agri-food studies in the Anglophone context. Much of the literature revolves around questions of how access to the land and resources to produce food can increase the ability to fulfil the food needs of low-income communities and communities of color, as well as the issue of food access in urban contexts. Less attention has been paid thus far to food preparation practices and culinary aspects. Against this background, we propose the concept of culinary justice, which links culinary practices and power, pointing to injustices in food provisioning and eating while also focusing on the symbolic and cultural components of food. Our central argument is that culinary elements and practices are important dimensions in questions about justice, as they enable a more nuanced understanding of socio-cultural, ecological, political, and historical food (in)equalities. Building on a review of existing approaches that touch upon the issues of culinarity and food justice in the areas of critical food studies, Black food studies, and postcolonial studies, we apply the concept of culinary justice to four contexts: private households, commercial restaurants, public catering, and community kitchens. In each area, we illustrate the role of food knowledge, care work, commensality, and spatial settings in issues of justice. As part of our contribution, we point toward future directions in food justice research, as well as future research needs in the practical field of food inequalities in culinary contexts.